Introduction of Case Based Learning Among First Professional MBBS Students in the Department of Biochemistry - Rachna Sabharwal (Dr. Annil Mahajan, 2021)
Introduction: In the traditional system of medical education, biochemistry was mainly taught by means of didactic lectures, tutorials and practical classes. It was teacher-centred, with minimal active participation from the students and hence, the students lacked critical thinking. These days, the education is changing to a student-centred teaching-learning process with the use of various innovative teaching methods. Case based learning (CBL) is one such approach which can make learning more effective and interesting and motivates the learner to gain knowledge. Purpose: To introduce the CBL in biochemistry at undergraduate level and to see its effectiveness in understanding the given concept. Material and Methods: The study was conducted among 150 MBBS first prof. students. Both, the faculty and students were sensitized to introduction of case-based learning methods. Theory lectures were taken for both the selected topics i.e., jaundice and diabetes mellitus. Then case-based learning sessions (CBL) were conducted for both the topics. At the end of both the lectures and CBL sessions, a post test (MCQ) was conducted. A repeat test was taken after 4 weeks from the first post-test (MCQ) for each topic. Also, the perceptions of students were taken on a pre-validated feedback questionnaire and analysed on 5-point Likert scale. Results: A total of 144/150 (96%) students participated in the study. The CBL scores were significantly higher than didactic lectures session scores (p <0.001). This difference was also seen in scores after four weeks of session completion (p <0.001). Student's feedback was taken on 5-point Likert scale feedback form which showed that 92% students either strongly agreed or agreed that topic was more interesting and easier when taught by CBL. Almost same number (92%) agreed to better understanding of topic and also that their attention span was more during CBL sessions. 87% students felt that it motivated them for self-study. 90% students agreed to have learnt teamwork during CBL sessions. 97% students agreed that CBL should be made a regular part of the curriculum. Conclusion: This study showed that case-based learning is an active method of learning resulting in better understanding and retention of subject of biochemistry.